MEMPELAJARI PEMANFAATAN AIR CUCIAN BERAS (Leri) PADA PROSES PEMBUATAN NATA DE LERI - M. Faiz Al Laily; Hapsari Titi Palupi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Due to its high nutrition, leri has a big potency to become bacterial growth media and nata. The study aims to find out the influence of coconut sugar concentration and the starter Acetobacter xylinum on the physical and chemical quality of nata de leri product. The research employs an experimental study using two factor, Factor 1 proportion that consist of four variable treatment, and each treatment was repeated three times. Proportion of washing rice (leri) 0%: water coconut 100% proportion of whasing 25% : water coconut 75% proportion washing rice 50% : water coconut 50% proportion washing rice 100% : water coconut 0%. The data analysis uses ANOVA. If it has a significant difference with a confidence interval 5% and 1%, if found influence on one of variable then continued with test of real small difference (BNT) 5%. Observations were performed with the best proportion of rice water and coconut water from physical properties with the result of nata de leri thickness test analysis at treatment (75% coconut water and 25% rice wash water) with 9.05mm thickness value. The best proportion of rice and coconut rice water from organoleptic properties with effectiveness index test was found in treatment (75% coconut water and 25% washing rice), 2,25 (somewhat like), aroma with value 2.50 (likes) , color with a value of 2.40 (like). The best proportion of rice and coconut rice water from physical and organoleptic properties with effectiveness index test was found in treatment (75% coconut water and 25% rice wash water), 2,25 (somewhat like), aroma with value 2.50 ( likes), color with a value of 2.40 (like).